Tipologi Resepsi Al-Qur’an dalam Tradisi Masyarakat Pedesaan: Studi Living Qur'an di Desa Sukawana, Majalengka - Yuliani, Yani (Al - Tadabbur: Jurnal Ilmu Al-Qur'an dan Tafsir, 2021)
The Qur'an is a holy book that contains theological and social teachings that function as a guide for humans to go to the path that is pleasing to God. However, when the Qur'an is present, consumed and received by the community, it is hoped that will experience various meanings which are implemented in various practices according to their respective and ideologies. This paper discusses the typology of the Qur’an reception in the community of Sukawana Village, Kertajati, Majalengka, West Java, and seeks to explore the meaning attached to the various receptions. The method used in this research is descriptive-qualitative and included in the type of fild research.  the author uses a phenomenological approach initiated by Edmund Husserl. This type of research is qualitative research, namely library research and field research at the same time. This study concludes that the typology of the reception of the Qur'an of the Sukawana community is in the form of exegesis receptions, aesthetic receptions, and functional receptions. When the Qur'an is received exegesis, the indicator is the understanding of the community that manifests in daily behavior by respecting and advising each other in terms of goodness. The Qur'an is also received and expressed as a holy book that contains elements of beauty so it is used as an accessory for the walls of mosques and houses (aesthetic reception). Also Sukawana community perceive the Qur’an functionally, so they believe that the Qur’an has magicial powers and it is often used as an instrument in mystical rituals.